2012
DOI: 10.1371/journal.pbio.1001309
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Requirements for Peroxisomal Targeting of Alanine-Glyoxylate Aminotransferase as an Essential Determinant in Primary Hyperoxaluria Type 1

Abstract: The crystal structure of the peroxisome enzyme alanine-glyoxylate aminotransferase bound to its targeting receptor Pex5p explains why even minor fold defects prevent targeting of the enzyme and cause kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
94
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(98 citation statements)
references
References 45 publications
4
94
0
Order By: Relevance
“…6) based on the known three-dimensional structures of human and trypanosome Pex5p (17,50). Besides protein and species-dependent amino acid variations of the PTS1 (9), the structure of the signal sequence seems to be very similar, as shown for SCP2 (sterol carrier protein 2), and the YQSKL peptide (16,17,59,60). Sites of interaction of human PEX5 with the PTS1 of SCP2 and AGT revealed five conserved asparagines at the ␣-helices of TPR3, TPR6, and TPR7 of Pex5p (21,59).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6) based on the known three-dimensional structures of human and trypanosome Pex5p (17,50). Besides protein and species-dependent amino acid variations of the PTS1 (9), the structure of the signal sequence seems to be very similar, as shown for SCP2 (sterol carrier protein 2), and the YQSKL peptide (16,17,59,60). Sites of interaction of human PEX5 with the PTS1 of SCP2 and AGT revealed five conserved asparagines at the ␣-helices of TPR3, TPR6, and TPR7 of Pex5p (21,59).…”
Section: Discussionmentioning
confidence: 99%
“…However, for none of these yeast proteins, the receptor interface has been defined in structural terms. Crystal structures of human PEX5-cargo complexes also revealed secondary binding sites, which were shown to increase the binding affinity to PEX5 (19,59,62). Although the interacting region of the cargo SCP2 is far apart from the PTS1-binding site, the second PEX5-binding site of AGT is next to its C terminus and thereby resembles that of Pcs60p.…”
Section: Analysis Of the Peroxisomal Targeting Signal Of Pcs60p-mentioning
confidence: 98%
See 2 more Smart Citations
“…Generally, peroxisomes are known to be highly variable in size, shape, number and protein content (Fransen 2012); nevertheless, to the best of our knowledge, a significant decrease in peroxisomal size after drug administration was not reported so far for mammalian cells. Interestingly, it is reported that peroxisomal proteins can be differentially localized within the cell depending on differential splicing, multiple targeting signals or phosphorylation (Fordor et al 2012;Ast et al 2013). However, dual localization of peroxisomal proteins was predominantly reported to occur into the cytosol and into mitochondria (Ast et al 2013), merely one study in yeast described nuclear translocation of a peroxisomal NAD + -dependent glycerol 3-phosphate dehydrogenase (Jung et al 2010).…”
Section: Discussionmentioning
confidence: 99%